The effect of implementing an automated oxygen control on oxygen saturation in preterm infants - Van Zanten, H A; Kuypers, K L A M; Stenson, B J; Bachman, T E; Pauws, S C; Te Pas, A B (Archives of disease in childhood. Fetal and neonatal edition, 2017)
OBJECTIVE: To evaluate the effect of implementing automated oxygen control as routine care in maintaining oxygen saturation (SpO2) within target range in preterm infants. METHODS: Infants <30 weeks gestation in Leiden University Medical Centre before and after the implementation of automated oxygen control were compared. The percentage of time spent with SpO2 within and outside the target range (90-95%) was calculated. SpO2 values were collected every minute and included for analysis when infants received extra oxygen. RESULTS: In a period of 9 months, 42 preterm infants (21 manual, 21 automated) were studied. In the automated period, the median (IQR) time spent with SpO2 within target range increased (manual vs automated: 48.4 (41.5-56.4)% vs 61.9 (48.5-72.3)%; p<0.01) and time SpO2 >95% decreased (41.9 (30.6-49.4)% vs 19.3 (11.5-24.5)%; p<0.001). The time SpO2<90% increased (8.6 (7.2-11.7)% vs 15.1 (14.0-21.1)%; p<0.0001), while SpO2<80% was similar (1.1 (0.4-1.7)% vs 0.9 (0.5-2.1)%; ns). CONCLUSIONS: During oxygen therapy, preterm infants spent more time within the SpO2 target range after implementation of automated oxygen control, with a significant reduction in hyperoxaemia, but not hypoxaemia.
Keywords: oxymetrie; neinvazivní ventilace; jednotky intenzivní péče o novorozence; Oxygen Inhalation Therapy; Preterm infant; Hyperoxaemia; Female; monitorování fyziologických funkcí; novorozenec; Monitoring, Physiologic; ženské pohlaví; Noninvasive Ventilation; Intensive Care Units, Neonatal; intratracheální intubace; lidé; Infant, Newborn; novorozenec nedonošený; Oximetry; Infant, Premature; prospektivní studie; Prospective Studies; Oxygen; Hypoxaemia; oxygenoterapie; Intubation, Intratracheal; kyslík; Humans